Primenenie kisloroda kak ergogenicheskogo sredsva v anaerobnykh glikoliticheskikh nagruzkakh y sportsmenok i sportsmenov - Gabrys, T.; Shmatlyan-Gabrys, U. (Teorija i Praktika fiziceskoj Kul'tury, 1999)
The aim of this study was to reveal the sex differences in effect of oxygen mixture's using in sports training of sprinters. 9 boys and 6 girls, athletes aged from 16 to 19 acted as subjects of our research. The efficiency of oxygen mixture's using in various regimes of rest intervals was discovered. As a result of the research it was stated that the use of oxygenous mixture influenced on boys and girls during training demonstrated the equal effect of their anaerobic working capacity's increase.